Economic Impact of Transport Infrastructure in Ethiopia: The Role of Foreign Direct Investment. (March 2023) - Badada, Bayissa; Delina, G.; Baiqing, Sun; Krishnaraj, Ramaswamy
This article examines the relevant relationship between transport infrastructure and foreign direct investment (FDI) in explaining economic growth from the road and air transport perspectives in Ethiopia over the period 1981 to 2017. To determine the economic effect of transport infrastructure, first, we assess the co-integration between transport infrastructure and economic growth using the autoregressive distributed lag bound test model. Once co-integration is established, the elasticity of economic growth is estimated using Ordinary Least Square estimation techniques. Second, we perform the hierarchical multiple regression to estimate the mediation impact of FDI in the association between transport infrastructure and economic growth. Initially, we have standardized all variables. Then, we estimate the mediating effect of FDI. To validate the consistency of our method, we check the robustness of our model. The obtained result shows that transport infrastructure has a significant long-term economic effect, and the short-run dynamics show the speed of adjustment is corrected by 81% each year toward the long-run path, and thereby transport infrastructure attracts FDI in Ethiopia. Moreover, FDI plays a significant mediating role, thereby increasing the economic growth performance of the country in Ethiopia. The study extends previous research and increases the validity of the findings by investigating the economic impact of transport infrastructure in the Ethiopian context. Moreover, this study is the first research study that explores the mediating role of FDI in the relationship between transport infrastructure and economic growth in Ethiopia.